Expression and Functional Roles of the Two Distinct NDH-1 Complexes and the Carbon Acquisition Complex NdhD3/NdhF3/CupA/Sll1735 in Synechocystis sp PCC 6803 - Zhang, Pengpeng (American Society of Plant Biologists, 2004)
To investigate the (co)expression, interaction, and membrane location of multifunctional NAD(P)H dehydrogenase type 1 (NDH-1) complexes and their involvement in carbon acquisition, cyclic photosystem I, and respiration, we grew the wild type and specific ndh gene knockout mutants of Synechocystis sp PCC 6803 under different CO(2) and pH conditions, followed by a proteome analysis of their membrane protein complexes. Typical NDH-1 complexes were represented by NDH-1L (large) and NDH-1M (medium size), located in the thylakoid membrane. The NDH-1L complex, missing from the ΔNdhD1/D2 mutant, was a prerequisite for photoheterotrophic growth and thus apparently involved in cellular respiration. The amount of NDH-1M and the rate of P700(+) rereduction in darkness in the ΔNdhD1/D2 mutant grown at low CO(2) were similar to those in the wild type, whereas in the M55 mutant (ΔNdhB), lacking both NDH-1L and NDH-1M, the rate of P700(+) rereduction was very slow. The NDH-1S (small) complex, localized to the thylakoid membrane and composed of only NdhD3, NdhF3, CupA, and Sll1735, was strongly induced at low CO(2) in the wild type as well as in ΔNdhD1/D2 and M55. In contrast with the wild type and ΔNdhD1/D2, which show normal CO(2) uptake, M55 is unable to take up CO(2) even when the NDH-1S complex is present. Conversely, the ΔNdhD3/D4 mutant, also unable to take up CO(2), lacked NDH-1S but exhibited wild-type levels of NDH-1M at low CO(2). These results demonstrate that both NDH-1S and NDH-1M are essential for CO(2) uptake and that NDH-1M is a functional complex. We also show that the Na(+)/HCO(3)(−) transporter (SbtA complex) is located in the plasma membrane and is strongly induced in the wild type and mutants at low CO(2).